IMF Survey, Volume 32, Issue 15. (IMF Survey; IMF Survey ;, 2003)
The IMF recently concluded its annual 'health checkup' (Article IV consultation with the U.S. authorities) of the U.S. economy amid continuing questions about the strength of the economic recovery. While recent data have been reassuring, IMF staff cautioned that lingering effects from the collapse of the equity price bubble could still dampen activity, so that a durable economic upswing was not a foregone conclusion. In view of the large unfunded liabilities in the public pension and health systems and the recent deterioration in the federal fiscal position, the staff also raised concerns about fiscal sustainability and pointed to the risk that fiscal deficits could crowd out private investment and exacerbate the growing U.S. current account deficit. These issues are discussed in the IMF Staff Report and Selected Issues papers now available on the IMF's website (http://www.imf.org/external/country/usa/index.htm).